2015
DOI: 10.1080/19420862.2015.1022692
|View full text |Cite
|
Sign up to set email alerts
|

An Fc engineering approach that modulates antibody-dependent cytokine release without altering cell-killing functions

Abstract: (2015) An Fc engineering approach that modulates antibodydependent cytokine release without altering cell-killing functions, mAbs, 7:3, 494-504, DOI: 10.1080DOI: 10. /19420862.2015 To link to this article: https://doi.org/10. 1080/19420862.2015 Cytotoxic therapeutic monoclonal antibodies (mAbs) often mediate target cell-killing by eliciting immune effector functions via Fc region interactions with cellular and humoral components of the immune system. Key functions include antibody-dependent cell-mediated cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 60 publications
2
33
0
1
Order By: Relevance
“…In Bacillus subtilis the pyr operon is regulated by the first gene of the operon, pyrR, through an autogenous transcriptional attenuation mechanism [37]. However, the E .…”
Section: Resultsmentioning
confidence: 99%
“…In Bacillus subtilis the pyr operon is regulated by the first gene of the operon, pyrR, through an autogenous transcriptional attenuation mechanism [37]. However, the E .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, selective enhancement of FcγRIIB binding was used to generate an anti-CD137 agonist with increased agonistic activity in vitro 257 . Individual FcRs have also been shown to exhibit differential contributions to cellular functions; for example, it has been demonstrated that FcγRI was largely responsible for secretion of both anti-inflammatory IL-10 258 and pro-inflammatory cytokines 259 . A suggested implication of this findings was that macrophage-mediated ADCC and ADCP could potentially be uncoupled from antibody-dependent cytokine release (ADCR), a feat which was accomplished recently by Kinder et.…”
Section: Expert Opinion: Is It Possible To Selectively Increase Samentioning
confidence: 99%
“…A suggested implication of this findings was that macrophage-mediated ADCC and ADCP could potentially be uncoupled from antibody-dependent cytokine release (ADCR), a feat which was accomplished recently by Kinder et. al., using an Fc-engineering approach to modulate cytokine release while leaving cell-killing activity intact 259 . The ability to selectively fine-tune or prevent cytokine release thus opens the possibility of limiting cytokine-related adverse events without losing effector capacity and tumoricidal activity.…”
Section: Expert Opinion: Is It Possible To Selectively Increase Samentioning
confidence: 99%
“…The sources of the anti-hinge Abs have been AHAs isolated from human serum, 14 a monoclonal anti-hinge mAb, 48 immunization-derived immune responses to peptide analogs of the cleaved hinge, 47 and proteinase-resistant versions of a monoclonal anti-hinge mAb. 53 The anti-hinge antibodies bind to the cleaved primary antibodies on the cell surface to provide an intact hinge and Fc that are capable of restoring ADCC and complement against the cancer cells. (b) Quantitative assessments of ADCC by intact and single-cleaved trastuzumab and the anti-hinge mAb 2095–2 alone and in combination with the scIgG.…”
Section: Engineering Proteinase-resistant Mabsmentioning
confidence: 99%